2022
DOI: 10.1017/s135561772200008x
|View full text |Cite
|
Sign up to set email alerts
|

NIH Toolbox® Episodic Memory Measure Differentiates Older Adults with Exceptional Memory Capacity from those with Average-for-Age Cognition

Abstract: Objective: Older adults with exceptional memory function, designated “SuperAgers,” include individuals over age 80, with episodic memory at least as good as individuals ages 50s–60s. The Northwestern University SuperAging cohort is defined by performance on an established test of verbal memory. The purpose of this study was to determine if superior verbal memory extends to nonverbal memory in SuperAgers by examining differences in the National Institutes of Health Toolbox® (NIHTB) between older adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…68 Interestingly, analyses of the cognitive profiles of older adults with exceptional verbal episodic memory revealed that they also demonstrated better performance than average memory controls on measures of non-verbal episodic memory, working memory and attention but not across other domains including processing speed, executive function, language and visuospatial measures. 42,52 Verbal episodic memory is vulnerable to ageing but concentrating on exceptional performance in this or other single cognitive domains especially at a single time point may provide limited insight into processes of cognitive ageing in super-agers.…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…68 Interestingly, analyses of the cognitive profiles of older adults with exceptional verbal episodic memory revealed that they also demonstrated better performance than average memory controls on measures of non-verbal episodic memory, working memory and attention but not across other domains including processing speed, executive function, language and visuospatial measures. 42,52 Verbal episodic memory is vulnerable to ageing but concentrating on exceptional performance in this or other single cognitive domains especially at a single time point may provide limited insight into processes of cognitive ageing in super-agers.…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%